The effects and mechanisms of isoliquiritigenin loaded nanoliposomes regulated AMPK/mTOR mediated glycolysis in colorectal cancer - Gang Wang; Yang Yu; Yu-Zhu Wang; Pei-Hao Yin; Ke Xu; Heng Zhang (Artificial Cells, Nanomedicine, and Biotechnology)
In this study, isoliquiritigenin (ISL) incorporated nanoliposomes were prepared and their effects on colorectal cancer (CRC) cell lines were investigated. Herein, we sought to explore the anti-cancer mechanisms of ISL loaded nanoliposomes (ISL-NLs) on AMP-activated protein kinase/mammalian target of rapamycin (AMPK/mTOR) pathways mediated glycolysis. Also, the key targets such as caveolin 1 (CAV1), glucose transporters and Akt/mTOR that promote glycolysis, and are activated via the induction of α-enolase (ENO1), fructose bisphosphate aldolase A (ALDOA) and monocarboxylate transporter 4 (MCT4) expressions were also investigated. It was shown that ISL-NLs significantly suppressed the proliferation and glucose uptake of CRC cell by potentially regulating the glycolysis and lactate targets as well as pathways that formed the basis of the anti-CRC effects of ISL-NLs. The mechanism underlying this effect was further validated via the regulation of some key targets such as ENO1, ALDOA, lactate dehydrogenase A (LDHA) and MCT4 in glycolysis coupled with cellular myelocytomatosis oncogene (c-myc), hypoxia-inducible factor 1-alpha (HIF-1α) in protein kinase B/mTOR (Akt/mTOR) pathways. Moreover, the AMPK proteins were identified to be up-regulated while the lactic acid production was suppressed by ISL-NLs in the CRC cells, indicating that ISL-NLs had an inhibitory effect on AMPK mediated glycolysis and lactate production. Altogether, these results have provided insights into the mechanism underlying the key role that liposomal ISL played in the multiple inhibition of AMPK and Akt/mTOR mediated glycolysis and lactate generation, which may be regulated as the alternative metabolic pathways of CRC as well as serve as adjuvant therapy for the disease.